Poisonous plants and related toxins - Acamovic, T.; Pennycott, T. W.; Stewart, C. S.; Ebooks Corporation (Wallingford : CABI, 2004)
This book present edited papers from the 6th International Symposium on Poisonous Plants, held in Scotland in August 2001. It covers a range of topics from plan biochemistry to toxic effects in animals (particularly grazing farm animals) and humans.
Contenido: Chapter 6 Bacteria and Corynetoxin-like Toxins in Nematode Seed-galls in Festuca nigrescens from North America and New ZealandChapter 7 Preliminary In Vitro Studies of Cistus salvifolius Leaves in Relation to Metabolic Disorders in Sheep; Chapter 8 Fusarochromanone and Wortmannin: Novel Fusarium Toxins; Chapter 9 Improved Methods for the Extraction and Purification of Coryneto
Libro electronico adquirido a perpetuidad con la editorial CABI
Keywords: GANADO -- PLANTAS VENENOSAS